Turning White: Co-Opting a Profession through the Myth of Progress, An Intersectional Historical Perspective of Brown v. Board of Education - Jennifer L. Martin; Jennifer N. Brooks (Educational Considerations, 2020)
The U.S. is currently experiencing a teacher shortage. Many school districts have been impacted by this issue and want to know: how do we recruit more qualified candidates into the profession, and, more importantly, how do we recruit more Teachers of Color? We may be experiencing a shortage of teachers in general, but there has been a paucity of Teachers of Color, particularly Black teachers, for decades. Looking back to the Brown v. Board decision (1954) to integrate public schools, thousands of Black teachers were pushed out of their jobs in various ways. In this article, we examine how this historical and groundbreaking decision had unintended negative consequences for Black teachers at the time of the decision and in the decades to follow. We speculate about the consequences for past, present, and future Students of Color with little to no exposure to and experience with Black teachers. Finally, we theorize intersectional solutions to the teacher shortage in general. Bringing issues of race to the forefront of our conversations about teaching is critical, but rare. According to Douglass Horsford (2019), “race remains not only a difficult and unwelcome topic among educators but also among education researchers, which perhaps leads to its undertheorizing in the field” (p. 262).
Keywords: Brown v. Board; Critical Race Theory; educational trauma; intersectionality; teacher shortage; unintended effects of Brown; white flight